2004
DOI: 10.1021/ma035523g
|View full text |Cite
|
Sign up to set email alerts
|

Polystyrene- and Poly(3-vinylpyridine)-Grafted Magnetite Nanoparticles Prepared through Surface-Initiated Nitroxide-Mediated Radical Polymerization

Abstract: Polymer-grafted magnetite (Fe3O4) nanoparticles (diameter about 10 nm) were prepared through a direct polymer grafting reaction from their surfaces. The chemisorbed initiator (TEMPO-based alkoxyamine) for nitroxide-mediated radical polymerization with a phosphoric acid group gave controlled polystyrene (PS) and poly(3-vinylpyridine) (P3VP) graft layers on the surface. The graft densities of polymers on the surfaces of magnetite particles were estimated at 0.12−0.20 chains/nm2 by thermogravimetric analysis (TGA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
141
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 213 publications
(143 citation statements)
references
References 43 publications
1
141
0
1
Order By: Relevance
“…[32][33][34][35][36] The M n of the corresponding free polymer were estimated to be approximately 14,000-30,000 by PMMA- standard calibration on a SEC using HFIP as an eluent. The relationship between M n and the thickness of the brush are shown in Figure 1.…”
Section: Results and Disscusionmentioning
confidence: 99%
“…[32][33][34][35][36] The M n of the corresponding free polymer were estimated to be approximately 14,000-30,000 by PMMA- standard calibration on a SEC using HFIP as an eluent. The relationship between M n and the thickness of the brush are shown in Figure 1.…”
Section: Results and Disscusionmentioning
confidence: 99%
“…Table 1 lists the M n s and MWDs of free polymers determined by SEC. The authors have previously found that the grafted polymer chains possess almost the same M n and MWD as those of the free polymers based on SEC measurement of the grafted polymers cleaved from the Fe 3 O 4 surface by acidic hydrolysis [32]. Accordingly, the M n and MWD of polymer brushes on TiO 2 nanoparticle were evaluated by SEC measurements of the corresponding free polymers, suggesting that controlled NMRP successfully proceeds from surface-immobilized TP and the free initiator at the same rate of propagation.…”
Section: Preparation and Physicochemical Properties Of Highdensity Pomentioning
confidence: 98%
“…1 The formation of P-O-M bonds was detected by IR and XPS spectra, indicating the anchoring of TP on the surfaces of the metal oxide nanoparticles. Surface-initiated NMRP of styrene and 3VP from nanoparticles was carried out as shown in our previous report [32] (Scheme 2). Table 1 lists the M n s and MWDs of free polymers determined by SEC.…”
Section: Preparation and Physicochemical Properties Of Highdensity Pomentioning
confidence: 99%
“…TEMPO-based alkoxyamine with a hydroxy group 15,16 was prepared as previously reported. 1-[Isocyanatopropyldimethylsilyl]-3,5,7,9,11,13,15-heptacyclopentylpentacyclo[9.5.1.1 3;9 .1 5;15 .1 7;13 ]octasiloxane (POSS-NCO) was purchased from Aldrich Chemical Co. Styrene and deuterated styrene were purchased from commercial sources and purified by distillation under reduced pressure over calcium hydride.…”
Section: Methodsmentioning
confidence: 99%